The potential of Spent Substrate of Oyster (Pleurotus ostreatus) dan Shiitake (Lentinula edodes) Mushrooms to Control Damping-off Disease (Rhizoctonia solani) in Tomato - Lia Herawati; Noor Istifadah (CROPSAVER, 2018)
Spent mushroom substrates are potential for controlling plant diseases. This study examined the abilities of spent substrates of Shiitake (L. edodes) and Oyster (P. ostreatus) mushrooms to inhibit the growth of R. solani in vitro and control damping-off disease in tomato seedling. The in vitro experiment examined the abilities of water extract of spent mushroom substrate non-sterile and sterile to inhibit the pathogen using poisonous food method. In the nursery experiment, substrates were mixed with the planting medium, 1:1, 1:2, and 1:3 (v/v). The result showed that the water extract of spent substrates of L. edodes and P. ostreatus inhibited the growth of R. solani by 29.1% – 40.6%. Non sterile water extract of spent substrate of P. osteratus showed highest inhibition level (40%). In tomato nursery, mixing  spent substrates of L. edodes or P. ostreatus with planting medium 1:2, and 1:3 (v/v) inhibited damping-off disease in tomato seedling by 57.5% - 100%.  Application of P. ostreatus spent substrate in the planting medium, 1:2 and 1:3 (v/v) resulted in 100% inhibition of the disease.Key words: tomato seedlings, water extract, spent mushroom substrate, in vitro